A Data-Driven Approach to Exploring Future Land Use and Transport Scenarios: The Online What If? Tool. Issue 2 (2nd April 2020) - Pettit, Christopher; Biermann, Sharon; Pelizaro, Claudia; Bakelmun, Ashley
ABSTRACT: In an era of rapid urbanization, there is a need for data-driven tools to guide long-term strategic planning. Online What If? ( OWI ) is a planning support system (PSS) that helps inform strategic planners about the impact of population growth and other socioeconomic factors will have on the future growth of cities. This research presents its application in metropolitan Perth with a two-part case study, demonstrating a first comprehensive application of the tool. First, OWI tests five scenarios for urban growth through the year 2050, allocating residential land use. Next, OWI alters land use allocations to align residential development with high frequency public transit, while also allocating commercial land use to support higher residential densities. Together, these data-driven scenarios inform city planners and policy makers in guiding the long-term, sustainable growth of Perth. The paper concludes with a review of OWI 's strengths, weaknesses and possibilities for continual development.